2015
DOI: 10.23907/2015.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Diphenhydramine-Related Accidental Overdose Deaths

Abstract: Characteristics of diphenhydramine (DPH)-induced accidental overdose deaths were compared to deaths without DPH present. Data from 4702 drug-induced deaths during 2005 to 2011 in four states were reviewed, with 3884 of these certified as accidental. DPH was involved in 276 cases (5.9%), with the manner of death ruled accidental in 181 (DPH group). The remaining 3703 accidental deaths constituted the control group. Age, body mass index, and the cases with benzodiazepine or opioid co-intoxicants did not differ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As a result, even though some of the individual associations appear to be fairly small, their possible additive contributions in opioid-related deaths could be substantial. For example, a previous analysis of DPH deaths found that over half of the DPH-related fatalities involved four or more drugs, with antidepressants often found as cointoxicants (8). Thus, in a hydrocodone-related death with a concentration of 0.08 μg/mL found on toxicological analysis, if DPH, a TCA, and alprazolam were also found to be cointoxicants, the additive effects of those cointoxicants in our model (−0.028 + −0.016 + −0.022), respectively, on the hydrocodone concentration might be comparable to an actual hydrocodone concentration of 0.146 μg/mL, almost double the concentration actually found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, even though some of the individual associations appear to be fairly small, their possible additive contributions in opioid-related deaths could be substantial. For example, a previous analysis of DPH deaths found that over half of the DPH-related fatalities involved four or more drugs, with antidepressants often found as cointoxicants (8). Thus, in a hydrocodone-related death with a concentration of 0.08 μg/mL found on toxicological analysis, if DPH, a TCA, and alprazolam were also found to be cointoxicants, the additive effects of those cointoxicants in our model (−0.028 + −0.016 + −0.022), respectively, on the hydrocodone concentration might be comparable to an actual hydrocodone concentration of 0.146 μg/mL, almost double the concentration actually found.…”
Section: Discussionmentioning
confidence: 99%
“…Cointoxicants often present with opioids in drug-related deaths include benzodiazepines, alcohol, and antidepressants (5)(6)(7). Diphenhydramine was also found to be a cointoxicant in almost 6% of West Virginia drug-induced deaths (8). It is well known that alcohol and drugs with central nervous system depressant effects can exert additive or synergistic toxic effects when used in conjunction with opioids (5).…”
Section: Introductionmentioning
confidence: 99%